Composite current collector, preparation method thereof and battery
By introducing hole structure, carbon nanotube array and Cu2Se nanoarray into the composite fluid collection, the problem of low conductivity of existing composite fluid collection is solved, and the fast charging capability and safety of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202411894211.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
The low conductivity of existing composite fluid collectors leads to a reduced fast charging capability of lithium-ion batteries and may occur lithium-ion excision behavior, affecting battery safety.
A composite fluid collector is employed, and its structure includes a base film, a copper layer, a hole structure, a carbon nanotube array and a Cu2Se nanoarray. The conductive and mechanical strength are improved by forming a copper layer on the base film, etching the holes, constructing a carbon nanotube array on the surface of the holes, and forming a Cu2Se nano-array on its surface.
It significantly reduces the internal resistance after the battery cycle, improves the battery's fast charging capability, and effectively suppresses the lithium surface of the negative electrode, improving the battery's safety performance.
Smart Images

Figure BDA0005201312370000131 
Figure BDA0005201312370000141 
Figure BDA0005201312370000142
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a composite current collector and a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion battery technology originated in the 1950s and has a long history of development. It matured and began to be commercialized on a large scale in the 1970s. Lithium-ion batteries have the advantages of high energy density, high power density, long cycle life, and environmental friendliness, and are widely used in new energy vehicles, energy storage equipment and other fields. The current collector is an indispensable component of lithium-ion batteries. Its main function is to carry the active materials of the battery and collect the current generated by the active materials of the battery to form a larger current output.
[0003] Since the density of polypropylene (PP) or polyethylene terephthalate (PET) is lower than that of copper foil or aluminum foil, in order to improve the energy density, the industry uses composite current collectors. The existing composite current collectors are a "sandwich" structure of metal layer + polymer base film layer + metal layer. For example, the middle layer is a polymer base layer such as polypropylene (PP) and polyethylene terephthalate (PET), and the outer layer is copper foil or aluminum foil. The composite current collector can make up for the lack of energy density, but the insufficient conductivity of polypropylene (PP) and polyethylene terephthalate (PET) reduces the fast charging ability of the battery, and even serious lithium plating occurs, leading to safety accidents. Therefore, it is urgent to solve the problem of low conductivity of the composite current collector. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a composite current collector and a preparation method thereof, and a battery. The composite current collector can significantly reduce the internal resistance of the battery after cycling, improve the fast charging capability of the battery, and effectively inhibit lithium deposition on the negative electrode surface.
[0005] In the first aspect of the present invention, the present invention proposes a composite current collector, including: a base film, a copper layer, the copper layer is located on at least one surface of the base film; the surface of the copper layer has holes; a carbon nanotube array, the carbon nanotube array is located on the surface of the holes; and a Cu2Se nanoarray, the Cu2Se nanoarray is located on the surface of the carbon nanotube array.
[0006] By forming a copper layer on the base film, a conventional current collector is prepared, and then further forming holes on the copper layer, the hole structure can greatly increase the contact area of the composite current collector surface, further improve the pole piece peeling strength, and provide sufficiently high mechanical strength and mechanical support for the next step of the composite current collector processing. The surface of the hole has a regular and orderly carbon nanotube array. The carbon nanotube array has a strong electronic conductivity, and the "array"-shaped conductive network is constructed in the present invention, which can greatly improve the conductivity of the composite current collector, significantly reduce the pole piece resistance, and support high current fast charging. And the cross-linked structure of the carbon nanotube array can provide space for the deposition of metallic lithium, can guide the precipitated metallic lithium to deposit uniformly and dissolve reversibly, and fully cope with the situation where high-rate charging causes the precipitation of metallic lithium. The Cu2Se nanoarray has high electronic conductivity and lithium affinity, cooperates with the carbon nanotube array, improves the fast charging capability, and inhibits the precipitation of metallic lithium at the graphite negative electrode. Therefore, the composite current collector having a pore structure, a carbon nanotube array and a Cu2Se nanoarray can significantly reduce the internal resistance of the battery after cycling, improve the fast charging capability of the battery, and effectively inhibit lithium plating on the negative electrode surface.
[0007] In some embodiments, the holes satisfy at least one of the following:
[0008] (a) The depth of the hole is 0.05 μm to 1 μm;
[0009] (b) The pore size is 20 μm to 100 μm;
[0010] (c) Based on the copper layer, the area of all holes formed is 60% to 80%.
[0011] In some embodiments, the nanotube array satisfies at least one of the following:
[0012] (i) The diameter of the carbon nanotube array is 10 μm to 50 μm;
[0013] (ii) Based on the area of all holes formed, the total area of all carbon nanotube arrays is ≥ 50%.
[0014] In some embodiments, the thickness of the Cu2Se nanoarray is 0.05 nm to 0.5 nm.
[0015] In a second aspect of the present invention, the present invention provides a method for preparing a composite current collector, comprising the following steps:
[0016] forming a first copper layer on at least one side of the base film;
[0017] forming holes on the surface of the first copper layer;
[0018] Forming a carbon nanotube array on the surface of the hole;
[0019] Cu2Se nanoarrays are formed on the surface of the carbon nanotube arrays.
[0020] By forming a first copper layer on at least one side of the base film, a current collector is prepared, and then holes are further formed on the copper layer. The holes can greatly increase the contact area of the composite current collector surface, further improve the pole piece peeling strength, and provide sufficiently high mechanical strength and mechanical support for the next step of the composite current collector processing. The carbon nanotube array is formed on the surface of the hole, which can greatly improve the conductivity of the composite current collector, thereby significantly reducing the pole piece resistance and supporting high current fast charging. In addition, the cross-linked structure of the carbon nanotube array can provide space for the deposition of metallic lithium, guide the precipitated metallic lithium to deposit uniformly and dissolve reversibly, and fully cope with the situation where metallic lithium is precipitated due to high rate charging. The Cu2Se nanoarray has high electronic conductivity and lithium affinity, cooperates with the carbon nanotube array, improves the fast charging capability, and inhibits the precipitation of metallic lithium on the graphite negative electrode. As a result, the composite current collector having a hole structure, a carbon nanotube array and a Cu2Se nanoarray can significantly reduce the internal resistance of the battery after cycling, improve the fast charging capability of the battery, and effectively inhibit the occurrence of lithium precipitation on the negative electrode surface.
[0021] In some embodiments, the method of forming holes on the surface of the first copper layer includes at least one of laser etching and chemical etching.
[0022] In some embodiments, in forming holes on the surface of the first copper layer, the control parameters include:
[0023] (1) The depth of the hole is 0.05 μm to 1 μm;
[0024] (2) The pore size is 20 μm to 100 μm;
[0025] (3) Based on the first copper layer, the area of all holes is 60% to 80%.
[0026] In some embodiments, the method of forming the carbon nanotube array on the surface of the hole includes at least one of a chemical vapor deposition method, a high temperature annealing method, and a hydrothermal method.
[0027] In some embodiments, in forming the carbon nanotube array on the surface of the hole, the control parameters include:
[0028] (A) The diameter of the carbon nanotube array is 10 μm to 50 μm;
[0029] (B) Based on the area of all holes formed, the growth area of all carbon nanotube arrays is ≥50%.
[0030] In some embodiments, forming a Cu2Se nanoarray on the surface of a carbon nanotube array comprises the steps of:
[0031] forming a second copper layer on the surface of the carbon nanotube array;
[0032] A selenium source is deposited onto the surface of the second copper layer by chemical vapor deposition to form a Cu2Se nanoarray.
[0033] In some embodiments, the thickness of the Cu2Se nanoarray is 0.05 nm to 0.5 nm.
[0034] In some embodiments, the mass ratio of the selenium source to the copper forming the second copper layer on the surface of the carbon nanotube array is 1:50 to 1:200.
[0035] In a third aspect of the present invention, the present invention provides a battery, comprising the composite current collector of the first aspect, or the composite current collector obtained by the preparation method of the second aspect.
[0036] The battery has excellent capacity retention, fast charging capability and ability to inhibit lithium plating.
[0037] Compared with the prior art, the present invention has the following beneficial technical effects:
[0038] (1) The pore structure on the surface of the composite current collector can greatly increase the contact area of the composite current collector surface, further improve the electrode peeling strength, prevent the slurry coated on the foil surface from falling off and affecting the battery performance, and provide sufficiently high mechanical strength and mechanical support for the next step of composite current collector processing.
[0039] (2) The carbon nanotube array can significantly improve the conductivity of the composite current collector, significantly reduce the electrode resistance, and support high-current fast charging. In addition, the cross-linked structure of the carbon nanotube array can provide space for the deposition of metallic lithium, guide the deposited metallic lithium to deposit evenly and dissolve reversibly, and fully improve the situation of metallic lithium precipitation caused by high-rate charging.
[0040] (3) Cu2Se nanoarrays have high ionic conductivity, electronic conductivity and lithium affinity, and can cooperate with carbon nanotube arrays to significantly improve the fast charging capability of the battery and reduce the lithium plating behavior of the battery.
[0041] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0043] Figure 1 It is a schematic diagram of the battery capacity retention rate of Example 1, Comparative Example 5, Comparative Example 6 and Comparative Example 8 of the present invention;
[0044] Figure 2 The battery internal resistance test diagram of Example 1 and Comparative Example 8 of the present invention;
[0045] Figure 3 3C is a relaxation voltage curve diagram of Example 1 of the present invention during the 3C cycle;
[0046] Figure 4 The charge and discharge curve test diagrams of Comparative Examples 9 and 10 of the present invention;
[0047] Figure 5 The cross-sectional SEM images of the negative electrodes of Comparative Example 9 (Figure a) and Comparative Example 10 (Figure b) of the present invention after being fully charged are shown;
[0048] Figure 6 Schematic diagram of the composite current collector of Example 1 of the present invention, wherein Figure (a) is a schematic diagram of the composite current collector; Figure (b) is an enlarged view of the red frame of Figure (a), indicating the etched holes on the surface of the composite current collector. DETAILED DESCRIPTION
[0049] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0050] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0051] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0052] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0053] In the first aspect of an embodiment of the present invention, the present invention proposes a composite current collector, comprising: a base film, a copper layer, the copper layer is located on at least one surface of the base film; the surface of the copper layer has holes; a carbon nanotube array, the carbon nanotube array is located on the surface of the holes; and a Cu2Se nanoarray, the Cu2Se nanoarray is located on the surface of the carbon nanotube array.
[0054] By forming a copper layer on the base film, preparing the current collector, and further forming holes on the copper layer, on the one hand, the holes can increase the roughness of the current collector surface, and the peel strength of the current collector will increase with the increase of roughness; on the other hand, the presence of holes can also increase the surface area of the current collector, thereby increasing the contact area between the current collector and the slurry. Therefore, the holes can greatly improve the peel strength and contact area of the composite current collector surface, prevent the slurry coated on the foil surface from falling off and affecting the battery performance, and at the same time provide sufficiently high mechanical strength and mechanical support for the next step of the composite current collector processing.
[0055] The surface of the hole has a regular and orderly carbon nanotube array (CNTs). On the one hand, the carbon nanotube array has a strong electronic conductivity, and in the present invention, an "array"-shaped conductive network is constructed, which greatly improves the conductivity of the composite current collector, significantly reduces the electrode sheet resistance, supports large current fast charging, and improves the rate performance of the battery cell; on the other hand, the carbon nanotube array (CNTs) has high conductivity and specific surface area, which can keep the local reaction current density uniform, and the metal lithium will not form needle-shaped lithium dendrites during the nucleation and deposition process, but instead form a uniform lithium layer. In addition, the carbon nanotube array is in a "straight array shape", which reserves enough space to guide the uniform deposition of metal lithium. The conductive frame inside the array keeps the lithium metal connected to the carbon nanotube array to avoid the formation of dead lithium that cannot be dissolved. When the lithium precipitation reaction occurs, the carbon nanotube array guides the metal lithium to nucleate and grow on the electrode surface and dissolve reversibly, which fully copes with the situation where high-rate charging causes the precipitation of metal lithium.
[0056] Cu2Se nanoarray, on the one hand, Cu2Se has high electronic conductivity, and the Cu2Se on the surface of the carbon nanotube array presents an array shape, which broadens the electronic conductive network and cooperates with the carbon nanotube array to improve the fast charging capability; on the other hand, the binding energy between metallic lithium and Cu2Se is higher than the binding energy between metallic lithium and graphite, so Cu2Se exhibits a stronger lithium affinity. When the lithium precipitation reaction occurs, metallic lithium will be formed preferentially on the surface of the Cu2Se array, and the Cu2Se array will guide the uniform deposition and re-dissolution of metallic lithium, inhibiting the precipitation of metallic lithium at the graphite negative electrode.
[0057] Therefore, the composite current collector having a pore structure, a carbon nanotube array and a Cu2Se nanoarray can significantly reduce the internal resistance of the battery after cycling, significantly improve the fast charging capability of the battery and effectively inhibit lithium plating.
[0058] In some embodiments of the present invention, the base film includes but is not limited to at least one of polypropylene (PP), polyethylene terephthalate (PET) and polyimide (PI), and further, the base film is polypropylene (PP) and polyethylene terephthalate (PET).
[0059] In some embodiments of the present invention, the base film has a thickness of 3 μm to 10 μm, and further, the base film has a thickness of 4 μm.
[0060] In some embodiments of the present invention, the copper layer has a thickness of 0.005 μm to 2 μm, and further, the copper layer has a thickness of 1 μm.
[0061] In some embodiments of the invention, the holes satisfy at least one of the following:
[0062] (a) The depth of the hole is 0.05 μm to 1 μm;
[0063] (b) The pore size is 20 μm to 100 μm;
[0064] (c) Based on the copper layer, the area of all holes formed is 60% to 80%.
[0065] The depth of the holes is 50nm to 1μm. On the one hand, it ensures that the cross-section of the current collector has sufficient conduction area to improve its conductivity and rate performance; on the other hand, it ensures that the current collector has good peel strength to prevent the slurry coated on the foil surface from falling off and affecting battery performance.
[0066] Exemplarily, the depth of the holes is 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm and 1 μm.
[0067] The pore size is 20 μm to 100 μm, which can effectively increase the specific surface area and enhance the peel strength without etching more foil and reducing the conductivity of the current collector.
[0068] Illustratively, the pore sizes are 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm and 100 μm.
[0069] Taking the copper layer as the benchmark, the area formed by all holes is 60% to 80%, and the total area of the outer surface of the holes facing outward is 60% to 80%, which represents the coverage rate of the holes on the surface of the foil. This area can effectively enhance the peeling strength of the electrode and prevent the slurry from falling off and affecting the battery performance.
[0070] Illustratively, based on the copper layer, the areas where all holes are formed are 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78% and 80%.
[0071] In some embodiments of the invention, the nanotube array satisfies at least one of the following:
[0072] (i) The diameter of the carbon nanotube array is 10 μm to 50 μm;
[0073] (ii) Based on the area of all holes formed, the total area of all carbon nanotube arrays is ≥ 50%.
[0074] The diameter and area of the carbon nanotube array will affect the electrode peeling force. If they are controlled within a reasonable range, the conductivity and cycle retention rate of the battery cell can be improved, and the occurrence of lithium plating can be effectively reduced.
[0075] Illustratively, the diameters of the carbon nanotube array are 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and 50 μm.
[0076] In some embodiments of the present invention, the thickness of the Cu2Se nanoarray is 0.05 nm to 0.5 nm.
[0077] The thickness of the Cu2Se array will affect the electrode peeling force. The thickness of the Cu2Se nanoarray is 0.05nm~0.5nm, which can work synergistically with the carbon nanotube array to further reduce and improve the conductivity and cycle retention rate of the battery cell, and effectively reduce the occurrence of lithium plating.
[0078] Exemplarily, the thickness of the Cu2Se nanoarray is 0.05 nm, 0.1 nm, 0.15 nm, 0.2 nm, 0.25 nm, 0.3 nm, 0.35 nm, 0.4 nm, 0.45 nm, and 0.5 nm.
[0079] In a second aspect of the embodiment of the present invention, the present invention provides a method for preparing a composite current collector, comprising the following steps:
[0080] forming a first copper layer on at least one side of the base film;
[0081] forming holes on the surface of the first copper layer;
[0082] Forming a carbon nanotube array on the surface of the hole;
[0083] Cu2Se nanoarrays are formed on the surface of the carbon nanotube arrays.
[0084] By forming a first copper layer on at least one side of the base film, a current collector is prepared, and then holes are further formed on the copper layer. The holes can greatly increase the contact area of the composite current collector surface, further improve the pole piece peeling strength, and provide sufficiently high mechanical strength and mechanical support for the next step of the composite current collector. The surface of the hole forms a carbon nanotube array, which can greatly improve the conductivity of the composite current collector, thereby significantly reducing the pole piece resistance and supporting high current fast charging. In addition, an "array"-shaped conductive network is constructed in the present invention, which can guide the precipitated metallic lithium to deposit uniformly and dissolve reversibly, and fully cope with the situation where metallic lithium is precipitated due to high-rate charging. The Cu2Se nanoarray has high ionic conductivity, electronic conductivity and lithium affinity, and cooperates with the carbon nanotube array to improve the fast charging ability and inhibit the precipitation of metallic lithium at the graphite negative electrode. As a result, the composite current collector having a hole structure, a carbon nanotube array and a Cu2Se nanoarray can significantly reduce the internal resistance of the battery, improve the conductivity, improve the fast charging ability of the battery and effectively inhibit lithium precipitation.
[0085] In some embodiments of the present invention, the method of forming a first copper layer on at least one side of a base film comprises: bombarding a copper target by magnetron sputtering technology of physical vapor deposition under the protection of argon gas to sputter a copper layer onto the base film.
[0086] In some embodiments of the present invention, the base film has a thickness of 3 μm to 10 μm; and the first copper layer has a thickness of 0.005 μm to 2 μm.
[0087] In some embodiments of the present invention, in forming a first copper layer on at least one side of the base film, the process parameters are controlled as follows: the argon flow rate is 20 sccm to 40 sccm; the sputtering pressure is 0.3 Pa to 1 Pa; the sputtering power is 30 W to 150 W; the copper target purity is ≥99.99%; and the argon purity is ≥99.99%.
[0088] In some embodiments of the present invention, the method of forming holes on the surface of the first copper layer comprises at least one of laser etching and chemical etching.
[0089] Laser etching has the advantages of high precision, high efficiency and non-contact processing, which can quickly form holes on the surface of the composite current collector, shorten the time and improve the overall efficiency; chemical etching has strong adaptability and good uniformity. Both etching methods can form holes on the surface of the first copper layer.
[0090] In some embodiments of the present invention, in forming holes on the surface of the first copper layer, the control parameters include:
[0091] (1) The depth of the hole is 0.05 μm to 1 μm;
[0092] (2) The pore size is 20 μm to 100 μm;
[0093] (3) Based on the first copper layer, the area of all holes is 60% to 80%.
[0094] The depth of the holes is 0.05 μm to 1 μm. On the one hand, it ensures that the cross-section of the current collector has sufficient conduction area to improve its conductivity and rate performance; on the other hand, it ensures that the current collector has good peel strength to prevent the slurry coated on the foil surface from falling off and affecting the battery performance.
[0095] Exemplarily, the depth of the holes is 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm and 1 μm.
[0096] The pore size is 20 μm to 100 μm, which can effectively increase the specific surface area and enhance the peel strength without etching more foil and reducing the conductivity of the current collector.
[0097] Illustratively, the pore sizes are 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm and 100 μm.
[0098] Taking the copper layer as the benchmark, the area formed by all holes is 60% to 80%, and the total area of the outer surface of the holes facing outward is 60% to 80%, which represents the coverage rate of the holes on the surface of the foil. This area can effectively enhance the peeling strength of the electrode and prevent the slurry from falling off and affecting the battery performance.
[0099] Illustratively, based on the copper layer, the areas where all holes are formed are 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78% and 80%.
[0100] In some embodiments of the present invention, the method of forming the carbon nanotube array on the surface of the hole comprises at least one of a chemical vapor deposition method, a high temperature annealing method and a hydrothermal method.
[0101] The chemical vapor deposition method can obtain carbon nanotube arrays with high purity, good density, low residual stress and good crystallization at a relatively low temperature; the high temperature annealing method can eliminate internal stress, stabilize the size, and reduce the deformation and crack tendency of the current collector; the carbon nanotube arrays synthesized by the hydrothermal method have high purity, good dispersibility and easy-to-control particle size.
[0102] In some embodiments of the present invention, in forming a carbon nanotube array on the surface of the hole, the control parameters include:
[0103] (A) The diameter of the carbon nanotube array is 10 μm to 50 μm;
[0104] (B) Based on the area of all holes formed, the growth area of all carbon nanotube arrays is ≥50%.
[0105] The diameter and area of the carbon nanotube array can improve the conductivity of the battery cell, reduce the local current density, and effectively reduce the occurrence of lithium plating.
[0106] Illustratively, the diameters of the carbon nanotube array are 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and 50 μm.
[0107] In some embodiments of the present invention, forming a Cu2Se nanoarray on the surface of a carbon nanotube array comprises the steps of:
[0108] forming a second copper layer on the surface of the carbon nanotube array;
[0109] A selenium source is deposited onto the surface of the second copper layer by chemical vapor deposition to form a Cu2Se nanoarray.
[0110] The purpose of forming the second copper layer on the surface of the carbon nanotube array is to deposit a copper layer on the surface of the carbon nanotube array to provide a material basis for the subsequent chemical reaction between the selenium source and metallic copper. The selenium source and copper react chemically under high temperature conditions to generate a Cu2Se nanoarray.
[0111] In some embodiments of the present invention, in forming the Cu2Se nanoarray, the control parameters are: reaction temperature is 200°C to 400°C, further, the reaction temperature is 200°C to 300°C; reaction time is 10min to 15min.
[0112] In some embodiments of the present invention, the method of forming a second copper layer on the surface of the carbon nanotube array includes: bombarding a copper target under the protection of argon gas by magnetron sputtering technology of physical vapor deposition to sputter a copper layer onto the carbon nanotube array.
[0113] In some embodiments of the present invention, the second copper layer has a thickness of 0.005 μm to 2 μm.
[0114] In some embodiments of the present invention, in forming the second copper layer on the surface of the carbon nanotube array, the process parameters are controlled as follows: the argon flow rate is 20 sccm to 40 sccm; the sputtering pressure is 0.3 Pa to 1 Pa; the sputtering power is 30 W to 150 W; the copper target purity is ≥99.99%; and the argon purity is ≥99.99%.
[0115] In some embodiments of the present invention, the thickness of the Cu2Se nanoarray is 0.05 nm to 0.5 nm.
[0116] The thickness of the Cu2Se array will affect the electrode peeling force. The thickness of the Cu2Se nanoarray is 0.05nm~0.5nm, which can work synergistically with the carbon nanotube array to further reduce and improve the conductivity and cycle retention rate of the battery cell, and effectively reduce the occurrence of lithium plating.
[0117] Exemplarily, the thickness of the Cu2Se nanoarray is 0.05 nm, 0.1 nm, 0.15 nm, 0.2 nm, 0.25 nm, 0.3 nm, 0.35 nm, 0.4 nm, 0.45 nm, and 0.5 nm.
[0118] In some embodiments of the present invention, the mass ratio of selenium to the copper of the second copper layer formed on the surface of the carbon nanotube array is 1:50 to 1:200.
[0119] The mass ratio of the selenium source to the copper forming the second copper layer on the surface of the carbon nanotube array determines the thickness of the Cu2Se nanoarray, and the thickness of the Cu2Se array will affect the electrode peeling force. If the Se:Cu mass ratio is reduced, the content of the Cu2Se nanoarray will be reduced, which will lead to limited effects in improving conductivity and inhibiting lithium precipitation. If the Se:Cu mass ratio is increased, the thickness of the Cu2Se nanoarray will increase, resulting in a decrease in the electrode peeling force, an increase in the internal resistance of the battery during the cycle, and a significant decrease in the capacity retention rate of the battery, inducing side reactions and causing severe lithium loss and lithium precipitation.
[0120] Exemplarily, the mass ratio of the selenium source to the copper forming the second copper layer on the surface of the carbon nanotube array is 1:50, 1:100, 1:150 and 1:200.
[0121] In a third aspect of the embodiments of the present invention, the present invention provides a battery, comprising the composite current collector of the first aspect, or the composite current collector obtained by the preparation method of the second aspect.
[0122] The battery has excellent capacity retention, fast charging capability and ability to inhibit lithium plating, which significantly improves the battery's service life and safety performance.
[0123] In some embodiments of the present invention, the battery further comprises a positive electrode plate, and the positive electrode plate adopts a conventional commercial lithium iron phosphate (LFP) plate.
[0124] In some embodiments of the present invention, the battery further comprises a negative electrode active material, which includes but is not limited to graphite or silicon-carbon composite materials.
[0125] In some embodiments of the present invention, the negative electrode active material further comprises a conductive agent, which comprises at least one of conductive carbon black, acetylene black, superconducting carbon and carbon dots.
[0126] In some embodiments of the present invention, the negative electrode active material further includes a binder, which includes but is not limited to at least one of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol and sodium carboxymethyl cellulose.
[0127] In some embodiments of the present invention, the negative electrode active material, the conductive agent, the binder, the thickener, and the solvent are mixed to prepare the negative electrode slurry, which is then stirred and coated on the composite current collector.
[0128] Furthermore, in the negative electrode slurry, based on the mass of the negative electrode slurry, the mass of the negative electrode active material accounts for 85% to 95%, the mass of the conductive agent accounts for 1% to 5%, the mass of the binder accounts for 1% to 5%, and the mass of the thickener accounts for 1% to 4%.
[0129] Furthermore, the negative electrode slurry has a surface density of 80 g / m 2 ~300g / m 2 .
[0130] In some embodiments of the present invention, the battery further comprises a separator, which includes but is not limited to at least one of glass fiber, polyethylene, polypropylene and polyvinylidene fluoride.
[0131] In some embodiments of the present invention, the battery further comprises an electrolyte, the electrolyte comprising a solvent, a lithium salt and a functional additive. The solvent comprises at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, ethyl acetate and ethyl propionate; the lithium salt comprises at least one of lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate and lithium difluorobisoxalate phosphate; the additive comprises at least one of lithium dioxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, 1,3-propane sultone, ethylene sulfate, ethylene carbonate, propylene sulfite, 1,4-butane sultone, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite, fluoroethylene carbonate, vinylene carbonate, fluoroethylene carbonate and lithium difluorophosphate.
[0132] In some embodiments of the present invention, the positive electrode sheet, the negative electrode sheet and the separator are made into a dry battery cell, and an electrolyte is injected to make a soft-pack battery cell.
[0133] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0134] Embodiment 1:
[0135] (1) Preparation of composite current collector
[0136] ① Conventional current collector preparation: Using the industrial standard PP base film with a thickness of 4.5μm, through magnetron sputtering technology, under the protection of argon, bombarding the copper target, sputtering metal copper on both sides of the base film to form the first copper layer, the thickness of the first copper layer on one side is 1μm, and the total thickness is 6.5μm. Control the magnetron sputtering process parameters: argon flow rate is 30sccm, sputtering pressure is 0.8Pa, sputtering power is 100W; copper target purity is ≥99.99%; argon purity is ≥99.99%.
[0137] ② Hole etching: The first copper layer on the base film is laser etched or chemically etched, the depth of the hole is 100μm; the hole diameter particle size is 50μm; based on the first copper layer, the area of all holes is 70%.
[0138] ③ Formation of carbon nanotube arrays: Carbon nanotube arrays are formed on the surface of the holes by chemical vapor deposition. The diameter of the carbon nanotube arrays is 20 μm. Based on the area of all holes formed, the growth area of all carbon nanotube arrays is 60%.
[0139] ④ Formation of the second copper layer: Through magnetron sputtering technology, under the protection of argon gas, the copper target is bombarded to sputter metal copper onto the surface of the carbon nanotube array to form a second copper layer with a thickness of 1μm. Control the magnetron sputtering process parameters: argon gas flow rate is 30sccm, sputtering pressure is 0.8Pa, sputtering power is 100W; copper target purity is ≥99.99%; argon gas purity is ≥99.99%.
[0140] ⑤ Formation of Cu2Se nanoarray: Selenium powder is deposited on the surface of the second copper layer by chemical vapor deposition, and reacts in a tube furnace at 250°C to form a Cu2Se nanoarray. The mass ratio of selenium to copper in the second copper layer is 1:100, and the thickness of the Cu2Se nanoarray is 0.2nm (see Figure 6 shown).
[0141] (2) Cell preparation
[0142] The negative electrode active material, conductive agent, binder, thickener and solvent are mixed to make negative electrode slurry, which is then coated on the composite current collector after stirring. The positive electrode sheet, negative electrode sheet and separator are then made into dry cells, which are then injected with electrolyte to make soft-pack cells with a capacity of 12.5Ah.
[0143] Embodiment 2:
[0144] The difference between Example 2 and Example 1: the diameter of the carbon nanotube array in Example 2 is 10 μm.
[0145] Embodiment 3:
[0146] The difference between Example 3 and Example 1: the diameter of the carbon nanotube array in Example 3 is 50 μm.
[0147] Embodiment 4:
[0148] The difference between Example 4 and Example 1: the diameter of the carbon nanotube array in Example 4 is 15 μm.
[0149] Embodiment 5:
[0150] The difference between Example 5 and Example 1: The diameter of the carbon nanotube array in Example 5 is 35 μm.
[0151] Embodiment 6:
[0152] The difference between Example 6 and Example 1: The carbon nanotube array area of Example 6 is 50%.
[0153] Embodiment 7:
[0154] The difference between Example 7 and Example 1: The carbon nanotube array area of Example 7 is 80%.
[0155] Embodiment 8:
[0156] The difference between Example 8 and Example 1: The carbon nanotube array area of Example 8 is 55%.
[0157] Embodiment 9:
[0158] The difference between Example 9 and Example 1: The carbon nanotube array area of Example 9 is 70%.
[0159] Embodiment 10:
[0160] The difference between Example 10 and Example 1: The thickness of the Cu2Se nanoarray in Example 10 is 0.05 nm.
[0161] Embodiment 11:
[0162] The difference between Example 11 and Example 1: The thickness of the Cu2Se nanoarray in Example 11 is 0.5 nm.
[0163] Embodiment 12:
[0164] The difference between Example 12 and Example 1: The thickness of the Cu2Se nanoarray in Example 12 is 0.1 nm.
[0165] Embodiment 13:
[0166] The difference between Example 13 and Example 1: The thickness of the Cu2Se nanoarray in Example 13 is 0.4 nm.
[0167] Comparative Example 1:
[0168] The difference between Comparative Example 1 and Example 1 is that the diameter of the carbon nanotube array in Comparative Example 1 is 5 μm, and based on the area formed by all holes, the growth area of all carbon nanotube arrays is 60%.
[0169] Comparative Example 2:
[0170] The difference between Comparative Example 2 and Example 1 is that the diameter of the carbon nanotube array in Comparative Example 2 is 70 μm.
[0171] Comparative Example 3:
[0172] The difference between Comparative Example 3 and Example 1: The thickness of the Cu2Se nanoarray in Comparative Example 3 is 0.01 nm.
[0173] Comparative Example 4:
[0174] The difference between Comparative Example 4 and Example 1 is that the thickness of the Cu2Se nanoarray in Comparative Example 4 is 1 nm.
[0175] Comparative Example 5:
[0176] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, no Cu2Se nanoarray is formed and no second copper layer is formed.
[0177] Comparative Example 6:
[0178] The difference between Comparative Example 6 and Example 1 is that no carbon nanotube array is formed in Comparative Example 6.
[0179] Comparative Example 7:
[0180] The difference between Comparative Example 7 and Example 1 is that there is no hole etching in Comparative Example 7.
[0181] Comparative Example 8:
[0182] The difference between Comparative Example 8 and Example 1 is that in the preparation of the composite current collector, only conventional current collector preparation steps are completed in Comparative Example 8.
[0183] Comparative Example 9:
[0184] The difference between Comparative Example 9 and Example 1: In Comparative Example 9, the battery components are assembled into button battery half-cells, and the assembly method is carried out according to the button battery assembly method well known in the art.
[0185] Comparative Example 10:
[0186] The difference between Comparative Example 10 and Comparative Example 8: In Comparative Example 10, the battery components are assembled into button battery half-cells, and the assembly method is carried out according to the button battery assembly method well known in the art.
[0187] Performance Testing
[0188] 1. Test Method
[0189] All embodiments and comparative examples 1 to 8 were subjected to a cell peel strength test, a cell disassembly test and an electrochemical performance test, and the specific test conditions are as follows:
[0190] 1. Peel strength test
[0191] Pressure-sensitive double-sided tape was pasted on the surface of the negative electrode and the stainless steel plate, the negative electrode and the stainless steel plate were fixed on a fixture, and then a peeling test was performed at a speed of 20 mm / min.
[0192] 2. Battery cell disassembly
[0193] After the long-term rate cycle test, the battery cell was disassembled to observe the surface condition of the negative electrode.
[0194] 3. Electrochemical performance test
[0195] a) Long-term rate performance test
[0196] First, discharge at a rate of 0.33C in the voltage range of 2.5V to 3.65V, and then cycle three times at a rate of 0.33C to set the battery capacity. At 25°C, charge at rates of 0.33C, 1C, 2C, 3C, and 4C in sequence, and discharge at a rate of 1C, with each charge rate cycled 100 times.
[0197] b) Relaxation monitoring of lithium deposition signal
[0198] After 100 cycles of each charging rate, the electrode was left to stand and observe the lithium deposition on the surface.
[0199] c) Internal resistance test
[0200] Electrochemical impedance spectroscopy (EIS) tests were performed on the batteries of the embodiments and comparative examples before and after cycling, and the impedance changes before and after 100 cycles were compared.
[0201] d) Button half-cell test
[0202] For the assembled button half-cell, the charging mode was set to capacity cutoff, charged to 500 mAh / g and cycled.
[0203] 2. Test Results
[0204] 1. Peel strength test results
[0205] The peel strength test results of the negative electrode sheets of the batteries of the embodiments and comparative examples are shown in Table 1.
[0206] Table 1 Test results of the battery negative electrode sheet peeling strength of the embodiment and the comparative example
[0207]
[0208]
[0209] From the peel strength test results in Table 1, it can be seen that compared with Comparative Example 7, Examples 1 to 13 show that the composite current collector after hole etching can significantly improve the peeling force of the pole piece, and the pole piece peeling force will be significantly reduced without hole etching. From Examples 1 to 13 and Comparative Example 8, it can be seen that if the performance of the composite current collector is to be improved, hole etching is required to improve the peeling force and reduce the influence of the formation of Cu2Se and carbon nanotube arrays on the pole piece peeling force.
[0210] The peeling force of Examples 1 to 13 is significantly greater than that of Comparative Examples 2 and 3. It can be seen that the diameter of the carbon nanotube array and the thickness of the Cu2Se nanoarray will affect the electrode peeling force. Increasing the diameter of the carbon nanotube array or increasing the thickness of the Cu2Se nanoarray will significantly reduce the peeling force. This is because when the diameter of the carbon nanotube array or the thickness of the Cu2Se nanoarray exceeds a certain range, it will directly affect the contact area between the negative electrode slurry and the negative electrode composite current collector, resulting in a decrease in the peeling strength.
[0211] 2. Long-term rate performance test results
[0212] The results of the soft-pack battery rate cycle test of the embodiment and the comparative example are shown in Table 2.
[0213] Table 2 Soft-pack battery rate cycle test results of the embodiment and the comparative example
[0214]
[0215]
[0216] It can be seen from the soft-pack battery cell rate cycle test results in Table 2 that the capacity retention rates of the various rate cycle test results of Examples 1 to 13 are all greater than the capacity retention rates of all comparative examples, indicating that the composite current collector of the present invention can significantly improve the high-rate capacity retention rate of the battery, and plays a good role in reducing the battery cycle internal resistance and improving the fast charging capability.
[0217] It can be seen from Examples 1 to 13 and Comparative Examples 1 and 2 that changing the diameter of the carbon nanoarray will reduce the capacity retention rate of the battery cell under high rate conditions.
[0218] It can be seen from Examples 1 to 13 and Comparative Examples 3 and 4 that changing the thickness of the Cu2Se nanoarray will also reduce the capacity retention rate of the battery cell under high rate conditions.
[0219] Depend on Figure 1 It can be seen that without the synergistic effect of Cu2Se nanoarrays and carbon nanotube arrays, the capacity retention rate will decrease, indicating that the positive synergistic effect of the two nanoarrays is better than the effect of a single substance in improving the performance of the composite current collector.
[0220] 3. Battery disassembly test results
[0221] The disassembly test results of the soft-pack batteries of the embodiment and the comparative example are shown in Table 3.
[0222] Table 3 Disassembly test results of soft-pack batteries in the embodiments and comparative examples
[0223]
[0224]
[0225] It can be seen from the disassembly test results of the soft-pack battery in Table 3 that lithium precipitation occurred to varying degrees in all embodiments and comparative examples. It can be seen from Examples 1 to 13 and Comparative Examples 7 and 8 that the composite current collector of the present invention is formed by pore treatment, carbon nanotube array and Cu2Se nanoarray, and the degree of lithium precipitation is significantly lighter than that of Comparative Examples 7 and 8. It can be seen from Examples 1 to 13 and Comparative Examples 5 and 6 that both carbon nanotube array and Cu2Se nanoarray are indispensable, and the two play a positive synergistic role, which well suppresses the lithium precipitation behavior of the graphite negative electrode, guides the uniform deposition of metallic lithium, and greatly reduces the risk of short circuit of the graphite negative electrode.
[0226] From Examples 1 to 13 and Comparative Examples 1 and 4, it can be seen that Comparative Examples 1 and 4 have slight lithium precipitation at a 3C charging rate, indicating that reducing the diameter and area of the carbon nanotube array, or reducing the thickness of the Cu2Se nanoarray, can protect the precipitation of metallic lithium on the graphite surface. However, combined with the capacity retention rates of Comparative Example 1 and Comparative Example 4 in Table 2, it can be seen that the capacity retention rates of both are lower than those of Example 1, indicating that reducing the diameter and area of the carbon nanotube array, or reducing the thickness of the Cu2Se nanoarray, has a weak ability of positive synergy. Although it can protect the precipitation of metallic lithium on the graphite surface, it will reduce the capacity retention rate of the battery cell, and does not have a good improvement on the overall performance of the battery.
[0227] It can be seen from Example 1 and Comparative Examples 2 and 3 that, in combination with the peeling strength, increasing the diameter of the carbon nanotube array, or increasing the thickness of the Cu2Se nanoarray, will reduce the peeling force of the electrode, and the electrode will fall off during the cycle of the battery cell. Both will significantly reduce the battery capacity retention rate, induce side reactions and cause serious lithium loss and lithium precipitation.
[0228] 4. Internal resistance test results
[0229] The test results of the internal resistance of the battery cells of the embodiments and comparative examples are shown in Table 4.
[0230] Table 4 Test results of internal resistance of battery cells of the embodiments and comparative examples
[0231]
[0232] It can be seen from the battery cell internal resistance test results in Table 4 that the battery cell internal resistance of the embodiments is smaller than that of the comparative examples, indicating that the composite current collector of the present invention can significantly reduce the battery cycle internal resistance and improve the fast charging capability of the battery.
[0233] From Example 1 and Comparative Example 8, it can be seen that the internal resistance of the battery cell of Example 1 is reduced by one time. Combining Comparative Examples 5 and 6, it can be seen that both the carbon nanotube array and the Cu2Se nanoarray are indispensable, and the two play a positive synergistic role, which can greatly broaden the electronic conductivity network, improve the electronic conductivity of the electrode, and reduce the internal resistance of the battery. Both the carbon nanotube array and the Cu2Se nanoarray will slightly increase the impedance value at the beginning of the cycle, but the internal resistance value of Comparative Example 8 without any treatment increases by about 2 times after the cycle ( Figure 2 ). The results show that the synergistic effect of carbon nanotube arrays and Cu2Se nanoarrays can greatly reduce the lithium deposition behavior of the graphite negative electrode during the cycle of the battery cell, and can induce the uniform deposition and re-dissolution of metallic lithium.
[0234] It can be seen from Example 1 and Comparative Examples 1 to 4 that changing the diameter and area of the carbon nanotube array, or changing the thickness of the Cu2Se nanoarray, will lead to an increase in the internal resistance of the battery cell.
[0235] 5. Relaxation monitoring lithium precipitation signal test results
[0236] Relaxation monitoring lithium precipitation signal test results are shown in Figure 3 .
[0237] Depend on Figure 3 It can be seen that the relaxation differential curve of Example 1 at the beginning of the 3C cycle (20 cycles) has detected the signal of metal lithium precipitation on the graphite surface, and the lithium precipitation signal is very strong at 40 cycles. After the soft-pack battery cell in Table 3 is disassembled, there is only slight lithium precipitation on the surface of the pole piece, indicating that most of the metal lithium precipitated during the charging process is dissolved again during the discharge process. After 100 cycles, only a very small amount of difficult-to-dissolve metal lithium or dead lithium is left on the surface of the pole piece. This shows that the composite current collector of the present invention has an excellent ability to inhibit the precipitation of metal lithium.
[0238] 6. Button half-cell test results
[0239] Depend on Figure 4 It can be seen that the capacity of comparative example 9 did not decay after 20 cycles, indicating that the precipitated metallic lithium can be uniformly deposited on the surface of the graphite negative electrode under the synergistic guidance of the carbon nanotube array and the Cu2Se nanoarray, and then deposited and dissolved again. However, the charging capacity of comparative example 10 decayed significantly, indicating that there was disordered deposition of metallic lithium ( Figure 5 ). This shows that the composite current collector of the present invention has an excellent ability to inhibit the precipitation of metallic lithium.
[0240] In this document, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0241] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A composite current collector, characterized in that: include: Basement membrane, A copper layer, wherein the first copper layer is located on at least one surface of the base film; and the surface of the copper layer has holes; A carbon nanotube array, wherein the carbon nanotube array is located on the surface of the hole; The Cu2Se nanoarray is located on the surface of the carbon nanotube array.
2. The composite current collector according to claim 1, characterized in that: The hole satisfies at least one of the following: (a) The depth of the hole is 0.05 μm to 1 μm; (b) the pore size is 20 μm to 100 μm; (c) Based on the copper layer, the area of all the holes formed is 60% to 80%.
3. The composite current collector according to claim 1, characterized in that: The nanotube array satisfies at least one of the following: (i) the diameter of the carbon nanotube array is 10 μm to 50 μm; (ii) Based on the area formed by all the holes, the total area of all the carbon nanotube arrays is ≥ 50%.
4. The composite current collector according to claim 1, characterized in that: The thickness of the Cu2Se nanoarray is 0.05nm-0.5nm.
5. A method for preparing a composite current collector, characterized in that: The following steps are involved: forming a first copper layer on at least one side of the base film; forming holes on the surface of the first copper layer; forming a carbon nanotube array on the surface of the hole; A Cu2Se nanoarray is formed on the surface of the carbon nanotube array.
6. The preparation method according to claim 5, characterized in that: The method of forming holes on the surface of the first copper layer includes at least one of laser etching and chemical etching.
7. The preparation method according to claim 6, characterized in that: In forming the holes on the surface of the first copper layer, the control parameters include: (1) The depth of the hole is 0.05 μm to 1 μm; (2) The pore size of the pores is 20 μm to 100 μm; (3) Based on the first copper layer, the area of all the holes is 60% to 80%.
8. The preparation method according to claim 5, characterized in that: The method for forming the carbon nanotube array on the surface of the hole includes at least one of a chemical vapor deposition method, a high temperature annealing method and a hydrothermal method.
9. The preparation method according to claim 8, characterized in that: In forming the carbon nanotube array on the surface of the hole, the control parameters include: (A) The diameter of the carbon nanotube array is 10 μm to 50 μm; (B) Based on the area of all the holes formed, the growth area of all the carbon nanotube arrays is ≥50%.
10. The preparation method according to claim 5, characterized in that: The forming of the Cu2Se nanoarray on the surface of the carbon nanotube array comprises the steps of: forming a second copper layer on the surface of the carbon nanotube array; A selenium source is deposited on the surface of the second copper layer by chemical vapor deposition to form a Cu2Se nanoarray.
11. The preparation method according to claim 10, characterized in that: The thickness of the Cu2Se nanoarray is 0.05nm-0.5nm.
12. The preparation method according to claim 10, characterized in that: The mass ratio of the selenium source to the copper forming the second copper layer on the surface of the carbon nanotube array is 1:50 to 1:
200.
13. A negative electrode sheet, characterized in that: The composite current collector comprises any one of claims 1 to 4, or the composite current collector is obtained by the preparation method of any one of claims 5 to 12.
14. A battery, characterized in that: Including the negative electrode sheet as claimed in claim 13.
Citation Information
Cited By
Lithium metal battery negative electrode current collector and total battery, half battery or symmetrical battery
CN120727834A